The Role of Sea Toll Shipping in Inter-Island Commodity Distribution: A Literature Review Study - Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The Sea Toll Program is a strategic initiative of the Indonesian government aimed at reducing price disparities and improving the distribution of goods between the western and eastern regions of the archipelago. This article presents a literature review study that examines the contribution of Sea Toll shipping to the distribution of commodities between islands through an analysis of various literature sources, policy documents, and secondary data. The results of the review indicate that Sea Toll plays an important role in strengthening national logistics connectivity, especially in the 3TP (underdeveloped, remote, outermost, and border) regions. This initiative has driven a decrease in distribution costs, opened market access for local business actors, and supported the smooth distribution of strategic commodities. However, the implementation of the program still faces obstacles, such as limited port infrastructure, imbalances in cargo flows (low return cargo), and lack of coordination between institutions. Other challenges include minimal involvement of the private sector and suboptimal utilization by local economic actors. Therefore, efforts are needed to increase synergy between the government, private sector, and the community, as well as the development of port facilities and production capacity in the destination areas. In conclusion, if managed well and sustainably, the Sea Toll shipping can be a main pillar in an efficient and equitable national logistics system, and can strengthen economic integration between regions in Indonesia.